SOME COMMENTS ON THE APPLICABILITY OF DIRECT COSTING TO DECISION MAKING. - Moss, Morton F.; Haseman, Wilber C. (The Accounting Review, 1957)
Abstract The article critically examines the aspects of direct costing. It discusses the development of the principle of burden application as the antecedent of direct costing. The article discusses the thinking of the absorption costing school as opposed to the ideas of direct costing which led to refinement involving the rate of activity in computing burden taxes, measurement of burden variances and use of separate burden rates for allocating fixed and variable portions of overhead. In contrast, direct costing school proposes an almost complete overthrow of the burden application principle. The article then describes the differences between direct costing and marginal costing, scrutinizing the techniques involved in obtaining both costs. The article then illustrates the shortcomings, discussing in length the instability of direct costing and the necessity of foresight into the future. The possibilities of direct costing in multi-product plant operations and its contribution to product pricing has been discussed in length. Restriction on cost and product flexibility, a result of too much reliance on differential cost analysis for price-output decisions and the factors involved in making long run price-output decisions by a firm operating within an oligopolistic market are detailed.